Efficacy of three key antiviral drugs used to treat orthopoxvirus infections: a systematic review - Joyce Yu; Suresh Mahendra Raj (University of New South Wales, 2019)
Background: In a global political climate increasingly concerned about terrorism, bioterrorism agents such as smallpox would undoubtedly be catastrophic. Since WHO announced the eradication of smallpox in 1980, consequently discontinuing the worldwide vaccination campaign, today's population is either immunologically naïve or has waning levels of protection. Further, up to 25% of today's population are contraindicated for smallpox vaccination due to various immunodeficiency conditions. The aim of this study was to evaluate the efficacy of the anti-DNA antivirals cidofovir (CDV), brincidofovir (BCV), and tecovirimat. As of July 2018, FDA approved tecovirimat as the first treatment for smallpox. Methods: A systematic review was conducted to identify relevant literature describing the efficacy and safety of CDV, BCV and tecovirimat 'in vitro, in vivo 'animal studies, human safety trials and human case reports of orthopoxvirus infection. Results: 158 studies met the inclusion criteria. CDV, BCV and tecovirimat are highly effective 'in vitro 'and 'in vivo 'animal studies when used therapeutically and prophylactically. They are partially protective in moderate, but not severe, immunodeficiency models. Clinical trials consistently report BCV and tecovirimat to be safe and well tolerated in humans. In human case reports, CDV, BCV and tecovirimat contributed to recovery from orthopoxvirus infection. BCV and tecovirimat demonstrate strong synergistic effect, and may reduce risk of antiviral-resistant strains. Conclusion: BCV and tecovirimat are particularly promising as anti-smallpox agents. Gaps in the literature indicate that further research should focus on developing more robust immunodeficiency and antiviral-resistance models.